PENGEMBANGAN MEDIA FLIPBOOK BERBASIS KEARIFAN LOKAL NGANJUK DALAM MENINGKATKAN MEMAKNAI KOSA KATA PADA PEMBELAJARANN BAHASA INDONESIA KELAS II DI SDN 3 KLODAN - Umbar Angzalna; Rian Damariswara; Kukuh Andri Aka (STKIP Subang, 2024)
The results of observations in class II at SDN 3 Klodan show that students have difficulty interpreting vocabulary in Indonesian language learning. Many students do not listen to the teacher's explanations and are less enthusiastic because there is no interactive, innovative and interesting teaching media. This research aims to create flipbook teaching media based on Nganjuk local wisdom to optimize student understanding. The research uses the R&D method with the ADDIE model. The data collected includes the validity, practicality and effectiveness of the Nganjuk local wisdom-based flipbook. Validation by material and media experts produced an average score of 85%, which is classified as very valid. The response from teachers showed an average score of 88%, while the student response reached 97.85%, which is very practical. The effectiveness test through question evaluation obtained results of 88.5% for limited trials and 90.3% for extensive trials, with an accumulative value of 89.4%, which shows that this media is very effective. In conclusion, flipbooks based on Nganjuk local wisdom are very effective in helping students understand vocabulary.